Telehealth experience during COVID-19 at an American burn Association (ABA) verified adult and pediatric burn center - Hannan A. Maqsood; Jacob M. Dougherty; Parker Martin; Zhaohui Fan; Cindy Wegryn; Stewart C. Wang; Gary A. Vercruysse; Mark R. Hemmila; Naveen F. Sangji (Elsevier, 2024)
Introduction: The COVID-19 pandemic resulted in unprecedented changes to healthcare services. Non-emergent, out-patient care was either discontinued, greatly reduced, or switched to telehealth during the first wave of the pandemic. Here, we describe an American Burn Association (ABA) verified Burn Center's experience with telehealth services during and after the COVID-19 emergency. Material and methods: In this retrospective study, all patients who underwent out-patient care at a large academic hospital's ABA Burn Center between March 2018 and March 2023 were identified from the electronic medical record system. Descriptive analysis was carried out to delineate trends in outpatient in-person and telehealth services during the COVID-19 pandemic. The travel distance saved from the introduction of telehealth was determined. Results: During the study period, 3471 patients underwent a total of 7444 out-patient visits for burn care. There were no telehealth visits prior to the onset of the COVID-19 pandemic. In the first year of the COVID-19 pandemic, 14.9% of all out-patient visits were conducted with telehealth. This decreased to 8.3% and 6.8% of all out-patient care in the second and third years of the pandemic, respectively. The average round trip travel distance saved was 123 miles (2.8---2312 miles). No complications were reported specific to receiving telehealth care. Conclusions: Telehealth is a feasible option for out-patient burn care in selected patients and reduces travel for patients. Further studies are needed to assess patient and clinician satisfaction, clinical outcomes, and the economic impact of telehealth utilization to help guide appropriateness of use.